Changes in the Prevalence of Asthma and Related Risk Factors in Adolescents: Three Surveys Between 1994 and 2015 - Mallol-Villablanca, E; Aguirre-Camposano, V (Elsevier Doyma, 2019)
Methods: This study assesses the temporal trend of current asthma symptoms prevalence and associated factors in Chilean adolescents from South-Santiago, considering surveys performed in 1994, 2002 and 2015. Results: The prevalence of current asthma symptoms showed a trend to increase from 11.1% in 1994 to 13.4% in 2015 (p < 0.001); physician-diagnosed asthma increased from 11.5% to 13.8%, (p < 0.001) whereas severe asthma and asthma with exercise decreased (p < 0.001). Female adolescents had a higher prevalence of current asthma in the three surveys (p < 0.001), and was a risk factor for asthma in the three surveys. In 2002, frequent consumption of meat and potatoes were associated with current asthma while frequent vigorous exercise was protective. Frequent exercise and parental tobacco smoking were risk for asthma in 2015 (p < 0.001). Current active tobacco smoking showed a trend to increase reaching a prevalence of 28.9% in 2015 (p < 0.001). There was a consistently low proportion of adolescents with current wheezing and asthma diagnosis (32.1% in 2015) and 37.6% of them had no asthma treatment. Conclusion: The prevalence of current asthma in adolescents from the studied area would be still increasing. As in other studies, female adolescents had a higher prevalence of current asthma. Current active tobacco smoking has strikingly increased in the studied children while indoor passive tobacco exposure remains inadmissibly high. Our findings suggest that asthma in children is underdiagnosed and undertreated. More attention should be given to female gender, tobacco exposure, air pollution and local diagnostic preferences when studying and interpreting trends of asthma prevalence in adolescents from developing localities. © 2018 SEICAP